2018
DOI: 10.1155/2018/6291082
|View full text |Cite
|
Sign up to set email alerts
|

Collision Avoidance Mechanism for Symmetric Circular Formations of Unitary Mass Autonomous Vehicles at Constant Speed

Abstract: Collective motion is a promising field that studies how local interactions lead groups of individuals to global behaviors. Biologists try to understand how those subjects interplay in nature, and engineers are concerned with the application of interaction strategies to mobile vehicles, satellites, robots, etc. There are several models in literature that employ strategies observed in groups of beings in nature. The aim is not to literally mimic them but to extract suitable strategies for the chosen application.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In the GCP law (2), let be k p = 0.4807, g p = 0.2300, and θ = 1.0747(rad). Then, the eigenvalues of the interconnection matrix A in (5) are obtained from (7), as illustrated in Figure 3(a). Because a pair of eigenvalues exists in the right-half-plane (RHP), the single-integratorlike agents of the multi-agent system, shown in Figure 2(a), diverge considerably from their expected behavior, which indicates that stability is not achieved.…”
Section: A Gcp Scheme and Its Application To Dynamic Multi-agent Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the GCP law (2), let be k p = 0.4807, g p = 0.2300, and θ = 1.0747(rad). Then, the eigenvalues of the interconnection matrix A in (5) are obtained from (7), as illustrated in Figure 3(a). Because a pair of eigenvalues exists in the right-half-plane (RHP), the single-integratorlike agents of the multi-agent system, shown in Figure 2(a), diverge considerably from their expected behavior, which indicates that stability is not achieved.…”
Section: A Gcp Scheme and Its Application To Dynamic Multi-agent Systemsmentioning
confidence: 99%
“…This strategy is frequently used in cases where multiple agents must move in a coordinated manner, for instance, to entrap a target, conduct patrolling and surveillance operations, and seek sources in a sensed environment (see [1] and the references therein). The method-based classification of schemes implemented in circular formation control is as follows: leader-follower method [2][3][4], artificial potential method [5], behavior-based method [6,7], virtual structure method [8,9], event-triggered control method [10], and cyclic pursuit method [11][12][13][14][15][16][17][18][19][20]. Among these schemes, the cyclic pursuit method has attracted considerable attention because of its intrinsic benefits resulting from its minimal communication requirements for connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Behavior-based Method [33,45,57,81,94,95,98,115] • Multiple expected and desired behavior is prescribed for every agent such as collision avoidance, obstacle avoidance, formation reconfiguration, target tracking, etc.…”
Section: Definitions Advantages Disadvantagesmentioning
confidence: 99%
“…It is shown that the collision avoidance is guaranteed if the solution of system (2) satisfies z i − z j > 0 for any pair i, j, i = j, t > 0 and the order preservation is achieved. The research study [95] proposed a collision avoidance strategy with phase-coupled oscillators dynamics to achieve the symmetric circular formations without collision. This problem is studied in networking techniques, such as ring topology, etc.…”
Section: Behavior-based Circular Formation Controlmentioning
confidence: 99%
See 1 more Smart Citation